EXTENT OF AVAILABILITY AND UTILIZATION OF LITERACY FACILITIES IN TEACHING AND LEARNING AMONG PUBLIC PRIMARY SCHOOLS IN UMUAHIA NORTH LGA OF ABIA STATE - Obasi, David C.; Anyachebelu, Faith E. (Journal of Early Childhood and Primary Education, 2020)
The aim of this study was to determine the extent of availability and utilization of literacy facilities in teaching and learning among public primary schools in Umuahia North Local Government Area, Abia State. The study was guided by five research questions and one hypothesis. The study adopted a survey design. The population of the study comprised of 694 public primary school teachers in the 45 public primary schools in Umuahia North L.G.A. Through simple random sampling techniques by balloting without replacement, 15 schools were selected out of the 45 public primary schools. The researchers also used simple random sampling techniques to sample 13 teachers from each of the 15 schools selected giving a total of 195 teacher respondents. The instrument for data collection was a 22-item structured questionnaire developed by the researchers titled â€œAvailability and Utilization of Literacy Facilities in Public Primary Schools Questionnaire (AULFPPSQ)â€. The instrument was validated by three experts. The reliability of the instrument was determined using Cronbach Alpha which yielded a reliability index of 0.76, 0.74, 0.78, 0.70, and 0.81 for the five clusters with an overall reliability of 0.75. The data was analyzed using mean scores. The findings from the study revealed that many literacy facilities ranging from audio, visual and audio-visuals were absent in public primary schools. Mostly available were visual facilities often used by teachers. The non-availability of these materials were due to lack of funds for purchase, location of some schools and activities of robbers in schools. Based on these findings, it was recommended that federal and state government should provide literacy facilities to public primary schools to enhance teaching and learning. It was also recommended that government should employ good security outfit to counter activities of robbers invading schools located in rural areas.
Keywords: literacy; Literacy facilities; teaching; learning